2004
DOI: 10.1111/j.0022-1112.2004.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Return migration of one‐sea‐winter Atlantic salmon in the River Tana

Abstract: Fifty-three one-sea-winter Atlantic salmon Salmo salar (45-63 cm L T ) were radio-tagged in the Tana fjord, Barents Sea, in 1995. Thirty-seven fish (70%) entered the freshwater zone of the River Tana in an average of 3 days after release in the fjord. The migration speeds in the lowest river section below the first riffle area were significantly higher than in the subsequent river section below the second riffle area. Similarly, the observed time spent in the first riffle area was significantly lower than in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 24 publications
3
50
0
Order By: Relevance
“…The reason may be that females actively searched for a suitable spawning site at different localities prior to spawning (Fleming 1996). Similar to our study, Karppinen et al (2004) found that wild females tended to exhibit a more erratic migration pattern than wild males, while Økland et al (2001) and Finstad et al (2005) did not find differences in movement patterns between wild males and females.…”
Section: Movement Patterns In the Pre-spawning Periodsupporting
confidence: 88%
“…The reason may be that females actively searched for a suitable spawning site at different localities prior to spawning (Fleming 1996). Similar to our study, Karppinen et al (2004) found that wild females tended to exhibit a more erratic migration pattern than wild males, while Økland et al (2001) and Finstad et al (2005) did not find differences in movement patterns between wild males and females.…”
Section: Movement Patterns In the Pre-spawning Periodsupporting
confidence: 88%
“…This finding is counter-intuitive: higher discharges usually result in higher velocities, which might be expected to impede movement, or at least increase energy used for migration and so reduce that available subsequently for spawning. However, in another study in Tana river, Karppinen et al (2004) found no significant correlation between discharge and migration. Thus, rather than assuming a consistent relation between discharge and upstream movement, there is a need to assess flow influences on a river-by-river basis.…”
Section: Discussionmentioning
confidence: 83%
“…Maximum net ground speeds recorded during undisturbed migration was 37 km day -1 in the Aberdeenshire Dee, 15 km day -1 in the River Laerdalselva, and 49 km day -1 for multi-sea-winter salmon and 47 km day -1 for grilse in the River Tana (Hawkins and Smith 1986;Økland et al 2001;Karppinen et al 2004;Finstad et al 2005). The highest migration rates were recorded early in the river migration phase and generally decreased as the fish approached the spawning ground in all four studies.…”
Section: Factors Affecting the Upstream Migration Patternmentioning
confidence: 87%
“…In generally undisturbed systems, the riverine migration of Atlantic salmon has been reported to take place in two or three successive phases before spawning: (1) a migration phase with steady progress upriver with periods of swimming alternating with stationary resting periods, (2) a search phase with movements both up and down river at or close to the position held at spawning, followed by (3) a long residence period, also termed the holding phase (Hawkins and Smith 1986;Heggberget et al 1988Heggberget et al , 1996Karppinen et al 2004;Laughton 1989;Webb 1989;Baglinière et al 1990Baglinière et al , 1991Laughton 1991;Økland et al 2001;Finstad et al 2005). In the Norwegian River Tana, the number of resting periods during the upstream migration phase (0-9) increased with migratory distance, and the resting periods lasted on average 5-8 days (Økland et al 2001).…”
Section: Factors Affecting the Upstream Migration Patternmentioning
confidence: 99%